POLISEMI KATA ŻAKARA DALAM AL-QUR’AN - Muzaki, Mukhlash; Gina Najjah Hajidah (Institut Kariman Wirayudha Sumenep, 2025)
This scientific paper examines the diversity of meanings (polysemy) of the word żakara contained in the verses of the Qur'an. This scientific paper is written to find out the meaning of the word żakara both lexically, grammatically, and contextually. In compiling this scientific paper, the author used a qualitative method with a descriptive approach. The writing of this scientific work begins with comprehensive data collection. The data sources used are the digital Al-Qur'an with the translation version of the Ministry of Religion and the book of Ibn Kathir's interpretation to support contextual understanding and interpretation of verses. After data collection is complete, the author classifies the word